2011
DOI: 10.1038/cmi.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

CD47: a new player in phagocytosis and xenograft rejection

Abstract: Organ transplantation is limited by the availability of human donor organs. The transplantation of organs and tissues from other species (xenotransplantation) would supply an unlimited number of organs and offer many other advantages for which the pig has been identified as the most suitable source. However the robust immune responses to xenografts remain a major obstacle to clinical application of xenotransplantation. The more vigorous xenograft rejection relative to allograft rejection is largely accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…Several hematological and solid tumors also express CD47 and are thereby protected from phagocytes. Preclinical data using antibodies that blocked human CD47 showed increased tumor cell phagocytosis and remarkable tumor growth inhibition in several xenograft models in mice and other species . Similar effects have been reported in syngeneic mouse models .…”
Section: Boosting the Antitumoral Effects Of Macrophages By Tam Reprosupporting
confidence: 67%
“…Several hematological and solid tumors also express CD47 and are thereby protected from phagocytes. Preclinical data using antibodies that blocked human CD47 showed increased tumor cell phagocytosis and remarkable tumor growth inhibition in several xenograft models in mice and other species . Similar effects have been reported in syngeneic mouse models .…”
Section: Boosting the Antitumoral Effects Of Macrophages By Tam Reprosupporting
confidence: 67%
“…In this study, we have attempted to prolong survival of porcine XLTx in baboons by combined strategies, consisting of (i) utilizing 4 different genetically modified porcine lungs, especially focusing on the role of hCD47 expression in donor lung grafts, and (ii) utilizing an induction immunosuppressive regimen that is similar to that of the xeno‐kidney transplant model that has achieved an average of longer than 4‐month survival of life‐supporting GalT‐KO alone kidney grafts in baboons . In designing this strategy, we reasoned (i) that hCD47 expression might overcome problems caused by the known species incompatibility of porcine CD47 and the primate homolog of its ligand, signal regulatory protein alpha (SIRPα) and (ii) that hCD55 or hCD46 would mitigate the complement‐mediated effects of natural anti‐pig antibodies. We also tested whether vascularized thymic grafts from the same donors might facilitate prolonged xenograft lung survival by minimizing primate anti‐pig T‐cell responses .…”
Section: Introductionmentioning
confidence: 99%
“…They also recognize and reject allogeneic cells in transplant settings (bone marrow and solid organ transplants) via "missing self" recognition of allogeneic nonself. 63 The authors showed that transplantation of Non-Obese Diabetes (NOD) (H-2 g7 ) cell aggregates into Rag-/γc-/mice (H-2 b ) that are deficient for all adaptive cells, host monocytes responded to allogeneic NOD cells by differentiating into mature dendritic cells. 61 This is an emerging area of investigation, and progress in this area will have enormous impact in transplantation.…”
Section: Pathways To Innate Allorecognitionmentioning
confidence: 99%